Redox Balance Differentially Affects Biomechanics in Permeabilized Single Muscle Fibres—Active and Passive Force Assessments with the Myorobot - Mena Michael; Larisa Kovbasyuk; Paul Ritter; Michael B. Reid; Oliver Friedrich; Michael Haug (Cells, 2022)
An oxidizing redox state imposes unique effects on the contractile properties of muscle. Permeabilized fibres show reduced active force generation in the presence of H2O2. However, our knowledge about the muscle fibre’s elasticity or flexibility is limited due to shortcomings in assessing the passive stress–strain properties, mostly due to technically limited experimental setups. The MyoRobot is an automated biomechatronics platform that is well-capable of not only investigating calcium responsiveness of active contraction but also features precise stretch actuation to examine the passive stress–strain behaviour. Both were carried out in a consecutive recording sequence on the same fibre for 10 single fibres in total. We denote a significantly diminished maximum calcium-saturated force for fibres exposed to ≥500 µM H2O2, with no marked alteration of the pCa50 value. In contrast to active contraction (e.g., maximum isometric force activation), passive restoration stress (force per area) significantly increases for fibres exposed to an oxidizing environment, as they showed a non-linear stress–strain relationship. Our data support the idea that a highly oxidizing environment promotes non-linear fibre stiffening and confirms that our MyoRobot platform is a suitable tool for investigating redox-related changes in muscle biomechanics.